Evaluating Production of Cyclopentyl Tetraethers by Marine Group II Euryarchaeota in the Pearl River Estuary and Coastal South China Sea: Potential Impact on the TEX86 Paleothermometer - Wang, Jin-Xiang; Xie, Wei; Zhang, Yi Ge; Meador, Travis B.; Zhang, Chuanlun L. (Frontiers in Microbiology, 2017)
TEX86 [TetraEther indeX of glycerol dialkyl glycerol tetraethers (GDGTs) with 86 carbon atoms] has been widely applied to reconstruct (paleo-) sea surface temperature. Marine Group I (MG-I) Thaumarchaeota were thought to be the primary source of GDGTs constituting the TEX86 formula; however, recent research has suggested that Marine Group II (MG-II) Euryarchaeota may also contribute significantly to the GDGT pool in the ocean. Little is known regarding the potential impact of MG-II Euryarchaeota-derived GDGTs on TEX86 values recorded in marine sediments. In this study, we assessed the relationship between distributions of GDGTs and MG-II Euryarchaeota and evaluated its potential effect on the TEX86 proxy. Lipid and DNA analyses were performed on suspended particulate matter and surface sediments collected along a salinity gradient from the lower Pearl River (river water) and its estuary (mixing water) to the coastal South China Sea (SCS, seawater). TEX86-derived temperatures from the water column and surface sediments were significantly correlated and both were lower than satellite-based temperatures. The ring index (RI) values in these environments were higher than predicted from the calculated TEX86-RI correlation, indicating that the GDGT pool in the water column of the PR estuary and coastal SCS comprises relatively more cyclopentane rings, which thereby altered TEX86 values. Furthermore, the abundance of MG-II Euryarchaeota 16S rRNA gene in the mixing water was two to three orders of magnitude higher than those observed in the river or seawater. Significant linear correlations were observed between the gene abundance ratio of MG-II Euryarchaeota to total archaea and the fractional abundance of GDGTs with cyclopentane rings. Collectively, these results suggest that MG-II Euryarchaeota likely produce a large proportion of GDGTs with 1–4 cyclopentane moieties, which may bias TEX86 values in the water column and sediments. As such, valid interpretation of TEX86 values in the sediment record, particularly in coastal oceans, should consider the contribution from MG-II Euryarchaeota.